COGNITIVE MARKERS OF SHORT FICTION BY VASYL STEFANYK: THE ARTISTIC NARRATIVE OF A «SIMPLE TEXT» - Matsevko-Bekerska, Lidiia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim. Through the context of formation of the principles of cognitive narratology, the article makes an attempt at a (new) (re)reading of separate works by Vasyl Stefanyk as a leading representative of the literary canon, of the literary classic, being the center of the latest paradigmatics of humanitarian sense creation. Such an angle of view on the writer’s novella heritage is completely actualized, as it is based on the tasks of cognitive narratology. The research methods. The article employs a narratological, psychoanalytical and biographical methods of studying Vasyl Stefanyk’s creative work, the grounds of reader-response criticism, dominant markers of the writer’s novella poetics, particularly those directly connected with with storytelling forms of the account of the created fictional material by him. The research results. The analysis of separate poetical devices, frequently used by Vasyl Stefanyk in his novellas, gave an opportunity to reveal in them the regularities of unfolding a cognitive chain where threading questions with a subseqent outline of the horizon of answers is in agreement with the author’s search for universal narratives in his novellas. It is proved that Vasyl Stefanyk’s fictional world can be understood, in addition to other approaches, in the prism of combined narrative and cognitive strategies of presentation and reception. The scientific novelty lies in the fact that in the proposed research Vasyl Stefanyk’s literary-fictional heritage is examined through the prism of cognitive narratology in such a systematic and complex way, as a matter of fact, for the first time, that it has become one of rather effective ways of rereading the Ukrainian literary classic. Simultaneously, the article shapes new questions and attempts (also for the first time) at finding new, different, sometimes inconspicuous answers in the writer’s novella poetics that are extremely important and essential for cognizing the human psyche of Vasyl Stefanyk’s prose heroes, finally, for understanding intellectual-emotional vicissitudes that inevitably accompany the reading of his works. The practical significance. The obtained research results may be used for delivering courses of Ukrainian literature at educational establishments, for studying the creative works by Vasyl Stefanyk, whose fictional world is shown in the prism of amalgamation of narrative and cognitive strategies of presentation and reception, for researching modern ways of prosewriting in Ukrainian classic literature.